Immunological and Inflammatory Responses in Children Infected with Enterobius Vermicularis Attending Hawija General Hospital, Kirkuk, Iraq - Shakour, Sunbul Jalal (Journal of Discoveries in Applied and Natural Science, 2026)
Background & Objective: Intestinal parasitism due to Enterobius vermicularis (pinworm) is prevalent among children and induces immune and inflammatory responses. The goal of this study is to assess the effect of pinworm infection on serum level pro-inflammatory cytokines (IL-6, TNF-α, and IFN-γ), C reactive protein (CRP) and Total IgE among children attending Hawija General Hospital in Kirkuk-Iraq. Materials & Methods: This cross-sectional study was performed in Hawija General Hospital, Kirkuk, Iraq from June to September 2025. Participants were recruited from the pediatric outpatient clinics and laboratory units. Eighty-three patients with confirmed Enterobius vermicularis infection and 80 healthy controls were enrolled. In the early morning, parasitological samples were collected using the perianal adhesive tape (cellophane-tape) method, and 5 mL venous blood was extracted from each participant for immunological examination. Results: Elevation of IL-6 (28.72 ± 5.85 pg/mL), TNF-α (20.93 ± 5.02 pg/mL) and IFN-γ (26.45 ± 6.18 pg/mL), CRP (7.43 ± 2.11 mg/L) and total IgE (152.83 ± 48.61 IU/mL) was significant in infected children compared to controls (p < 0.001). Certain markers were influenced by age and BMI with mid-childhood (6–10 years) and obese children exhibiting greater inflammatory responses. The positive correlations among cytokines, CRP, and IgE signified coordinated systemic and humoral immune activation. Conclusions: Pinworm infection is correlated with a strong systemic inflammatory and IgE-mediated humoral response in children. Serum cytokines, CRP and IgE may be potential biomarkers for infection and disease monitoring.